Penguasaan Wilayah Dengan Cara Konflik Bersenjata, Perspektif Hukum Internasional - Ritsky Mendo Lisapasly; Josina Augustina Yvonne Wattimena; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This study discusses the case of territorial control by means of armed conflict.Purposes of the Research: to Analyze and Know About How To Acquire Territory Under International Law and To Analyze And Know About Territorial Control By Way Of Armed Conflict According To International Law. Methods of the Research: This research is a normative research. The approach used is a statutory approach. The legal sources used are primary legal materials, secondary legal materials and tertiary legal materials. Done by analyzing data qualitatively that is descriptive.Results of the Research: The results of this study indicate that there is territorial control by means of armed conflict, from the perspective of international law (Taliban Case in Afghanistan).